(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2021)
Security studies cannot escape the war and the process of warfare. The debates about the changed nature of war are as old as the very notion of war. The author asks the following questions: Is Clausewitz still relevant to the evolving concept of the battlefield?; What is the contribution of narratives on political violence and terrorism in the process of military mobilization?!; Can we and how can we study modern warfare through the lens of culture?! and Does war still exist in the eyes of international law?! In the analysis of war when the primary trinity (of Clausewitz) is used as an analytical framework, it becomes apparent that Clausewitz’s theory of war is broad and fluid enough to cover the entire military spectrum, including irregular non-state conflicts. The concept of narrative can contribute to the theory and research of the phenomena of terrorism, political violence, and radicalization. Exploration of the current significance of the concept of war includes issues essential to the prohibition on the threat of use of force or the use of force in Article 2 (4) of the Charter, in times of heightened will to use force as a foreign policy instrument. Questions about total war, the link between war and globalization, and the changes in warfare in the advanced industrial democracies of the West remain unanswered.